Trafficking of Women in International Migration: a Study of Indonesia and Malaysia Diplomacy - Sa'dan, Masthuriyah (Yayasan Jurnal Perempuan, 2015)
The lack access in knowledge, education, training and economic factor has made women and girls become prone-victims of trafficking. Malaysian Govt has reported that 4.268 sex commercial workers are coming from Indonesia. They are mostly trafficked via the borders of Malaysia and Indonesia. To cut the chain of violence, it is necessary to cut the whole syndicate of traffickers instead of one trafficker. International diplomacy between Indonesia and Malaysia is hoped to foster the reduction of human trafficking, specifically women and girls as way to advocate international gender instruments.